Study of InGaAsP/InP quantum well structures grown by solid source MBE and their application for long wavelength infrared light detection - Sun, Lu (2008)
The energy band dispersion relations for InGaAsP/InP multi quantum well (MQW) structures were investigated using 8x8 method. In this study, different strain cases in the well of the structures were investigated with well width and well doping concentration as parameters. The results give out the energy band structure for each case explicitly. To the best of our knowledge, it is the first study of InGaAsP/InP MQW energy band structure considering doping concentration, strain and well width effect at the same time.